Penggunaan Bakteri Kitinolitik sebagai Pengendali Hayati Colletotrichum capsici pada Tanaman Cabai - Dian Syahfitri; Nisa Rachmania Mubarik; Lisdar A Manaf (Jurnal Fitopatologi Indonesia, 2018)
Use of Chitinolytic Bacteria as Biological Control of Colletotrichum capsici on Chili PlantsColletotrichum capsici is known as the causal agent of anthracnose disease in chili plant and may cause reduction of crop yield. Chitinolytic bacteria, namely Serratia marcescens KAHN 15.12, Bacillus thuringiensis SAHA 12.12, and BAE 36 were reported to have antagonistic activity against C. capsici. Therefore, a study was conducted to determine the potential of chitinolytic bacteria on controlling C. capsici on chili plants in greenhouse experiment. Three bacterial isolates used as biocontrol agent was formulated by using talcum as carrier materials. The methodologies consisted of characterization of bacterial isolates, formulation of biocontrol agent, viability test of bacterial isolate, efficacy of biocontrol agents in the laboratory and in the greenhouse.  Disease severity in the laboratory reached 64% when chili treated with isolate formulation of BAE 36.  In the greenhouse, BAE 36 isolate formulation and consortium formulation were able to suppress infection of C. capsici; each was indicated by disease incidence of 25% and 50%, respectively. These results indicated that chitinolytic bacterial formulations could be potencial as biocontrol agents of C. capsici.